Online sustainable fashion brands: Millennials’ attitude, purchase intention and behaviour. - Tan, Hock Guan; Shuhaida, Md. Noor (2021)
Today’s fashion industry offers a wide variety of clothing at highly affordable prices, thus making clothing highly disposable. While the scenario encourages the growth of the fashion industry, it proves to be detrimental to the environment. Textile waste comprises 4% of the total waste in Malaysia, equivalent to 1,000 metric tons of textile waste per day. As such, there are growing calls for sustainable fashion consumption, leading to the growth of various online sustainable fashion brands, particularly those targeting millennials. In understanding this specific market, this study was guided by the Theory of Planned Behaviour to investigate the factors contributing to millennials’ attitude towards online sustainable fashion brands, their intention to purchase and their actual purchasing behaviour. Using convenience sampling, an online questionnaire was distributed to relevant WhatsApp and Facebook groups, resulting in 229 respondents for the study. The findings indicate that customers’ endorsement and ethical beliefs of sustainable fashion were the most significant predictors in influencing consumers’ attitude, followed by family environmental beliefs and celebrity endorsement. However, peer pressure, environmental concerns and subjective norms do not have a significant relationship with attitude. Additionally, perceived behavioural control also positively and significantly predicts attitude, purchasing intention and purchasing behaviour of sustainable fashion brands. Finally, the study shows conclusive relationships between attitude, purchasing intention and purchasing behaviour of sustainable fashion brands. The study’s theoretical contribution and practical implications are presented as well.